(1) y= - x² - 4x + 9 and (2) y + 5x = - 7. Isolate y in (2); y= - 5x - 7 (3)
Since (1) and (3) have the same value or the same y, then we can write:
(1)=(3)
- x² - 4x + 9 = - 5x - 7
-x² - 4x + 9 + 5x +7 = 0
-x² + x + 16 = 0 OR x² - x - 16 = 0
Solve this quadratic equation:
x' = [-b+√(b²-4ac)]/(2a) and x" = [-b-√(b²-4ac)]/(2a)
x' = [+1+√(-1)² - 4(1)(-16)]/2 → x' = [1+√(1+64)]/2 → x' = [1+√65)]/2
x" = [+1-√(-1)² - 4(1)(-16)]/2 → x' = [1-√(1+64)]/2 → x' = [1-√65)]/2
x' = [1+√65)]/2 = + 4.5311
x" =[1-√65)]/2 = - 3.5311
Answer:
1/6 = .16
Step-by-step explanation:
2/12 simplifies to 1/6
Answer:
Hi there!
The first one is not a function because it crosses twice using the vertical line test while the second one is a function.
Step-by-step explanation:
All I know is x is 81 degrees
Answer:
sorry but what is this I don't understand?